2018
DOI: 10.5380/rf.v48i4.50437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Education Level on Operator’s Perfomance With Harvester Virtual Reality Simulator

Abstract: The aim of this study was to analyze the effect of age and education level on performance of forest operators during the training with the harvester virtual reality simulator (HVRS). The study was performed in the Forest Operator Training Centre (CENFOR), of the Midwestern State University (UNICENTRO), located in the municipality of Irati, state of Paraná, Brazil. Data of 124 professionals trained in the HVRS were used. A specialized software was used to simulate machine operation, and operational performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Lopes et al (2008), infer that the optimization of operating techniques points to the evolution of the performance of machines and operators so that it is possible to increase the productivity of operations. The work carried out by Lopes et al (2018) aimed at determining the effect of age on the learning level of operators. They used a virtual reality simulator and concluded that the 23-37-yearold group is ideal for the best learning.…”
Section: Resultsmentioning
confidence: 99%
“…Lopes et al (2008), infer that the optimization of operating techniques points to the evolution of the performance of machines and operators so that it is possible to increase the productivity of operations. The work carried out by Lopes et al (2018) aimed at determining the effect of age on the learning level of operators. They used a virtual reality simulator and concluded that the 23-37-yearold group is ideal for the best learning.…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional technologies and virtual reality are used to simulate surgical procedures with robotic complexes [3], develop laparoscopic surgery skills for surgeons [4], train dentists [5], test resistance to motion sickness [6], simulate the process of controlling motor vehicles [7], aircraft, logging equipment [8], and sports training [9]. It is evident that, in terms of environment and subject of work perception, all these application areas of virtual environments are fundamentally different.…”
Section: Introductionmentioning
confidence: 99%